2018
DOI: 10.1111/cga.12308
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic findings and prognosis of craniosynostosis diagnosed during the fetal and neonatal periods

Abstract: The aim of the study was to explore the sonographic findings of fetuses with craniosynostosis and investigate their prognosis. We conducted a 5-year, multicenter retrospective study and collected data on patients with craniosynostosis diagnosed in the perinatal period. Of 41 cases, 30 cases (73%) were syndromic craniosynostosis, eight cases (20%) were non-syndromic craniosynostosis and the other three cases (7%) were secondary craniosynostosis of chromosomal deletion syndromes. The prenatal ultrasound detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
2
21
0
1
Order By: Relevance
“…In accordance to the literature, in all our cases of Apert syndrome, syndactyly of upper and partly of the lower extremities were diagnosed by ultrasound (Table 1 and Fig. 1c) [17,19,20]. In one case of fetal Saethre Chotzen syndrome, syndactyly was diagnosed only postnatally.…”
Section: Value Of Sonographic Signs: Other Malformationssupporting
confidence: 88%
See 2 more Smart Citations
“…In accordance to the literature, in all our cases of Apert syndrome, syndactyly of upper and partly of the lower extremities were diagnosed by ultrasound (Table 1 and Fig. 1c) [17,19,20]. In one case of fetal Saethre Chotzen syndrome, syndactyly was diagnosed only postnatally.…”
Section: Value Of Sonographic Signs: Other Malformationssupporting
confidence: 88%
“…In our case series, the diagnosis was suspected at the time of the second trimester screening in 9/13 patients and in 4/13 patients between 27 + 0 and 33 + 4 weeks of gestation. However, the diagnosis can be challenging as the extent of the skull deformity can vary and the standardized measurements of the head (biparietal diameter and head circumference) are not necessarily outside the normal range [17]. To confirm the diagnosis, it can be helpful to use a threedimensional ultrasonic skeletal imaging mode to image the Acrobrachycephaly, flat occiput, hypertelorism, flat forehead, midface hypoplasia, asymmetric cranial shape [24], turricephaly [5] Syndactyly, central nervous malformations (dysgenesis of corpus callosum, abnormal gyration) [5,24], neurological development disorders possible Crouzon syndrome Variable; often coronal and sagittal sutures [24] Acrobrachycephaly, (symmetric) midface hypoplasia, hypertelorism [24],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray et al 27 found a wide variation in the normal cephalic index during pregnancy, as did Kurmanavicius et al 28 and Constantine et al 12 who both examined a large number of normal fetuses. This contributes to the explanation as to why craniosynostosis is rarely diagnosed in the second trimester, unless there are other abnormalities present 3,5,25,29 …”
Section: Discussionmentioning
confidence: 99%
“…These two-dimensional (2D) planes allow identification of intracranial landmarks and acquisition of specific biometric measurements which, if absent or outside expected reference ranges, may be indicative of an anomaly. 2 Occasionally, it is not possible to obtain these planes, resulting in an incomplete or suboptimal assessment. 3 Advances in three-dimensional US (3D-US) and multi-planar reconstruction can complement conventional 2D-US and overcome some of its limitations.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%